The model predict bankruptcy of bank in Indonesia: macro and micro indicators - Novi Primita Sari; M. Faisyal Abdullah; Agung Prasetyo N.W (Jurnal Ekonomi Modernisasi, 2020)
This study aims to find the best model with a combination of macroeconomic variables and micro or internal variables of the bank itself to predict bankruptcy in Indonesian banks, especially state-owned banks represented by BRI Bank as the object of research. This research is a quantitative study using time series data using a regression analysis method where the selected macro and micro variables will be formed as models and tested for later analysis. There are two models used in this study, namely the Grover model and the Zmijewski model. The result of this research is to find an appropriate model to predict bankruptcy using macro and micro variables, and the best after the flow test is Grover's model. The groover model can produce a combination of macro and micro variables in accordance to investigate bankruptcy by proving that the macro variable that affects is the exchange rate, while from the micro side built by LDR, ROA, and company size.